Study on the movement of Rattus rattus and evaluation of the plague dispersion in Madagascar. - Rahelinirina, Soanandrasana; Duplantier, Jean Marc; Ratovonjato, Jocelyn; Ramilijaona, Olga; Ratsimba, Mamy; Rahalison, Lila (Vector-Borne and Zoonotic Diseases, 2010)
International audience Plague affects mainly the rural areas in the central highlands of Madagascar. Rattus rattus is the main rodent host of Yersinia pestis in these localities. Since the introduction of plague, endemic foci have continued to expand, and spatiotemporal variability in the distribution of human plague has been observed. To assess the movements of R. rattus and evaluate the risk of dispersion of the disease, a field study at the scale of the habitats (houses, hedges of sisals, and rice fields) in the plague villages was carried out during high and low seasons of plague transmission to humans. The systemic oral marker Rhodamine B was used to follow rats' movements. Baits were placed in different habitats, and trapping success was carried out once a month for 3 months after the bait distribution. Plague indicators (reservoirs' abundance, flea index, Y. pestis prevalence in fleas, and Y. pestis antibody prevalence in rats) were determined. The highest abundance of rats and marking efficiency were observed in the sisal hedges and the rice fields. Marked rats were captured most commonly near the points where baits were initially placed. The main movements of rats were observed between the houses and sisal hedges. Major differences were observed between the seasons of high and low plague transmission. During the season of low plague transmission, rats were more abundant in the sisal hedges and rice fields, with rats moving from the houses to the rice fields. During the high plague transmission season, rats moved from the hedges of sisal to the rice fields. Important indicators of vector abundance and plague transmission were higher during the high plague transmission season. The three study habitats were the risk areas for plague transmission, but the risk appeared highest in the houses and sisals. Rats' movements according to the season were likely directed by the availability of food.